Neuromorphic olfaction - Persaud, Krishna C.; Marco, Santiago; Gutiérrez, Agustín (Frontiers in neuroengineering., 2013)
Many advances have been made in the last decade in the understanding of the computational principles underlying olfactory system functioning. Neuromorphic Olfaction is a collaboration among European researchers who, through NEUROCHEM (Fp7-Grant Agreement Number 216916)-a challenging and innovative European-funded project-introduce novel computing paradigms and biomimetic artifacts for chemical sensing. The implications of these findings are relevant to a wide audience, including researchers in artifical olfaction, neuroscientists, physiologists, and scientists working with chemical s.